2018
DOI: 10.1073/pnas.1718793115
|View full text |Cite
|
Sign up to set email alerts
|

Flynn effect and its reversal are both environmentally caused

Abstract: Population intelligence quotients increased throughout the 20th century—a phenomenon known as the Flynn effect—although recent years have seen a slowdown or reversal of this trend in several countries. To distinguish between the large set of proposed explanations, we categorize hypothesized causal factors by whether they accommodate the existence of within-family Flynn effects. Using administrative register data and cognitive ability scores from military conscription data covering three decades of Norwegian bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 20 publications
3
71
0
5
Order By: Relevance
“…These studies suggest that there has been a transition in the relationship between intelligence and fertility over time, from no clear gradient among cohorts born in the first half of the twentieth century, to a small to moderate negative gradient (i.e. higher intelligence, lower fertility) for cohorts born in the second half of the twentieth century [6,18,20,21], though a minority of studies have reported positive gradients [17,22,23]. In general, studies have reported a steeper negative gradient for women than for men (e.g.…”
Section: (A) Previous Research On Intelligence and Fertilitymentioning
confidence: 99%
“…These studies suggest that there has been a transition in the relationship between intelligence and fertility over time, from no clear gradient among cohorts born in the first half of the twentieth century, to a small to moderate negative gradient (i.e. higher intelligence, lower fertility) for cohorts born in the second half of the twentieth century [6,18,20,21], though a minority of studies have reported positive gradients [17,22,23]. In general, studies have reported a steeper negative gradient for women than for men (e.g.…”
Section: (A) Previous Research On Intelligence and Fertilitymentioning
confidence: 99%
“…The combined contribution of all of these genomic variants to any group level difference in a complex human trait is predicted to be small, possibly spurious, and largely dependent on the environment according to population genetic theory (Rosenberg et al, 2018). Empirically, we also know that intergenerational scores on IQ tests have changed over time because of improvements in the human environment (Bratsberg & Rogeberg, 2018;Flynn, 1999) and the association of IQ with genetic factors depends heavily on environmental factors (Devlin, Daniels, & Roeder, 1997;Flynn, 1999;Turkheimer, Haley, Waldron, D'Onofrio, & Gottesman, 2003). To claim that racial inequality in education is immutable because of genetics is no less of distortion of scientific knowledge today than it was in the 1970s or 1930s.…”
mentioning
confidence: 99%
“…There is no consensus regarding the cause of the Flynn effect, but given the recent and rapid increase, genetic explanations are unlikely. Common hypotheses include increases in test familiarity, improvements in education, sophistication of the technological and media environment, better nutrition, decreasing family size, and increased out-breeding or 'hybrid vigor' (Bratsberg and Rogeberg 2018;Clark, Lawlor-Savage, and Goghari 2016;Nisbett et al 2012;Pietschnig and Voracek 2015; Trahan et al 2014;Johnson 2006). Flynn (2007) and Greenfield (1998; suggest that the effect is caused by a rapid worldwide increase of cultural practices, technologies, and environments that promote abstract cognitive processing as opposed to more traditional forms of concrete, pragmatic thinking.…”
Section: The Flynn Effectmentioning
confidence: 99%